A Smallest Singular Value Method for Solving Inverse Eigenvalue Problems (Journal of Computational Mathematics, 1996)
Utilizing the properties of the smallest singular value of a matrix, we propose anew, efficient and reliable algorithm for solving nonsymmetric matrix inverse eigenvalue problems, and compare it with a known method. We also present numericalexperiments which illustrate our results.